Work Satisfaction and Affective Commitment Among State Prison Officers - Desa, Nasina Mat; Hassan Asaari, Muhammad Hasmi Abu; Al-Assad Senafi, Mohd. Hafez (European Scientific Journal, ESJ, 2021)
Job satisfaction and affective commitment have been discussed by the scholar in the field. Moreover, the issues about job satisfaction, namely the job environment, salary, colleagues, promotion, and supervision were also an issue among state prison officers about their affective commitment. Thus, the paper’s objectives are to explore the relationship and understand the impact of the job satisfaction components toward affective commitment. Selfadministered questionnaires are distributed among 300 state prison officers. A total of 205 usable questionnaires are collected with a response rate of 68.3%. Reliability analysis is conducted before the analysis of the relationship and impact between variables. Furthermore, a new research framework is discovered. The study discovered the work environment, salary, and supervision as components of job satisfaction have an impact on state prison officers’ affective commitment. Unfortunately, state prison officers state that colleagues of job satisfaction have no significant impact on their affective commitment.